Big thrombus "sitting" in an atrial septal aneurysm. Issue 9 (30th May 2017) - Adauy, Julián Vega; Gabrielli, Luigi; Córdova, Samuel; Saavedra, Rodrigo; McNab, Paul
Abstract : A 79 year‐old‐man presented three episodes of upper gastrointestinal bleeding and weight loss. Endoscopy revealed bleeding and extrinsic compression at the pyloric region. Computed tomography scan showed a pancreatic tumor, peritoneal carcinomatosis, vascular infiltration, and incidentally found a partially calcified hypodense lesion of 35 mm in the left atrium, suggesting a myxoma or a thrombus. Echocardiography revealed moderate left atrium enlargement, dilated left atrial appendage with spontaneous echo contrast, moderate dilatation and dysfunction of the left ventricle, ejection fraction was 39%, and an atrial septal aneurysm in which a piriform, mass of 35×33×25 mm, was "sitting, " suggesting an organized thrombus.